Histamine H1 receptor deletion in cholinergic neurons induces sensorimotor gating ability deficit and social impairments in mice - Li Cheng (Nature Portfolio, 2021)
Social impairment and anhedonia are common negative symptoms in patients with schizophrenia. Here, the authors show that the histamine H1 receptor in cholinergic neurons in the basal forebrain has a critical role in sensorimotor gating, social behaviour, and anhedonia-like behaviour in mice.